A high Tg hydrocarbon resin, a resin composition for high-frequency copper-clad laminates, and a preparation method and use thereof
By using a high-polymerization Tg hydrocarbon resin to improve its crosslink density and aromatic structure ratio, the existing hydrocarbon resin has been solved, and the problems of poor heat resistance and low glass transition temperature in high-frequency copper clad plates are achieved. Dielectric properties, mechanical properties and dimensional stability.
Patent Information
- Application Number
- CN202310062576.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-18
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2043-01-18
AI Technical Summary
The existing hydrocarbon resins have disadvantages such as poor heat resistance, low glass transition temperature, insufficient rigidity and large thermal expansion coefficient in high-frequency printed circuit board applications, which limit their application in high-frequency copper clad plates.
Using a high Tg hydrocarbon resin with low polymerization (0-8), the cross-linking density and aromatic structure ratio of the resin are improved through specific chemical structure general formulas and preparation methods, thereby improving its heat resistance, mechanical strength and Dimensional stability.
The excellent performance of high Tg hydrocarbon resin in high-frequency copper clad plates has been achieved, including dielectric constant 2.57~2.68, dielectric loss 0.0009~0.0013, glass transition temperature 238~251℃, peel strength 1.09~1.28N/mm and Bending strength is 63~74MPa.
Smart Images

Figure CN116284692B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to organic polymer compounds, compositions and preparation and use thereof for electronic materials, and relates to a high Tg (Tg is glass transition temperature) hydrocarbon resin, a resin composition for high-frequency copper-clad laminates and a preparation method and use thereof. The high Tg hydrocarbon resin and the resin composition for high-frequency copper-clad laminates of the present invention are suitable for the field of high-frequency printed circuit boards. Background Art
[0002] With the advent of 5G (fifth-generation mobile communication technology), the frequency of signal transmission on printed circuit boards is getting higher and higher, and high-frequency copper-clad laminates have become a research hotspot in the current printed circuit board industry. In order to reduce the transmission loss in the high-frequency band and cope with high-temperature soldering and high-layer assembly during substrate installation, the insulating materials used for copper-clad laminates need to have better dielectric properties, heat resistance, glass transition temperature and dimensional stability.
[0003] In recent years, hydrocarbon resins such as polybutadiene resin, styrene-butadiene copolymer, ethylene propylene diene copolymer, cycloolefin copolymer, etc. have attracted much attention due to their small molecular chain polarity (the electronegativity of carbon atoms and hydrogen atoms is 2.5 and 2.1 respectively) and excellent dielectric properties (dielectric constant (1MHz) 2.4-2.8, tanδ 0.0002-0.0006). The prepreg with low thermal expansion and low dielectric loss and its application disclosed in CN101692756A and the method for preparing high-speed copper-clad laminates with bismaleimide-modified hydrocarbon resin disclosed in CN114589991A adopt polyolefin resin (polybutadiene, polystyrene, etc.) system to obtain copper-clad laminates with excellent dielectric properties and low water absorption. However, this type of hydrocarbon resin chain segment is extremely flexible and has poor adhesion to the substrate. The copper clad laminate made from it has disadvantages such as poor heat resistance, low glass transition temperature, insufficient rigidity and large thermal expansion coefficient. Even if resins with excellent properties such as heat resistance and mechanical properties (thermosetting polyphenylene ether, bismaleimide resin) are added during the application of the copper clad laminate, no obvious improvement effect can be achieved, which limits its application in high-frequency printed circuit boards. Summary of the invention
[0004] The purpose of the present invention is to overcome the deficiencies in the above-mentioned prior art and to provide a high-Tg hydrocarbon resin with good performance, a resin composition for high-frequency copper-clad laminates, and a preparation method and use thereof.
[0005] The present invention is a high Tg hydrocarbon resin, characterized in that the high Tg hydrocarbon resin has a chemical structure formula shown in (I):
[0006]
[0007] In formula (I): n = 0 to 8, R 1A hydrocarbon group having 6 to 30 carbon atoms and containing an aromatic ring structure;
[0008] The high Tg hydrocarbon resin is a mixture of compounds having the above chemical structural formula and a polymerization degree n of 0 to 8, wherein the mass proportion (ie, mass percentage) of the compound with n=0 is 25 to 68%.
[0009] The method for preparing the high Tg hydrocarbon resin described in the present invention is characterized by the following steps:
[0010] In a reaction bottle equipped with a stirrer, a thermometer and nitrogen, 1 mol of vinylbenzene diboric acid, 1.8-2.6 mol of alkyl halide, a capping agent of 1.05-1.45 times the molar amount of the alkyl halide, and a solvent A of 2-10 times the total mass of the alkyl halide and the vinylbenzene diboric acid are added, stirring is started at room temperature to dissolve the alkyl halide, the vinylbenzene diboric acid and the capping agent (completely), and then a catalyst of 2%-6% of the molar amount of the vinylbenzene diboric acid and a polymerization inhibitor of 0.03%-0.2% of the molar amount of the vinylbenzene diboric acid are added; an accelerator of 2 times the molar amount of the alkyl halide is (accurately) weighed, the accelerator is prepared into an accelerator aqueous solution with a mass percentage concentration of 5% with deionized water, and the aqueous solution is added to the reaction bottle, and the reaction is carried out at a temperature of 50-80° C. for 8-20 hours. After the reaction is completed, the reaction system is cooled to room temperature, and the organic phase is extracted with solvent B. The organic phase is washed with saturated sodium carbonate aqueous solution and washed with water until neutral, and then the solvent B is evaporated at 50-75°C to obtain a high Tg hydrocarbon resin.
[0011] The vinylphenyl diboronic acid is 5-vinylisophenyl diboronic acid;
[0012] The alkyl halide is a compound having 6 to 30 carbon atoms, containing an aromatic ring structure and being disubstituted by halogen;
[0013] The solvent A is any one of methanol, ethanol, tetrahydrofuran, dioxane, dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone;
[0014] The catalyst is any one of palladium chloride, palladium acetate, 4-triphenylphosphine palladium, carbene palladium, and ferrocene palladium dichloride;
[0015] The polymerization inhibitor is a hindered amine, which is any one of phenothiazine, 2,2,6,6-tetramethylpiperidine, p-phenylenediamine, naphthylamine, diphenylamine, 4-methylpyrimidine, N,N-diethyl-p-phenylenediamine, N,N-diphenyl-p-phenylenediamine, dioctyl diphenylamine, N-methyl-α-naphthylamine, etc.;
[0016] The end-capping agent is 3-vinylbenzene boronic acid or 4-vinylbenzene boronic acid;
[0017] The solvent B is any one of toluene, xylene, methyl isobutyl ketone, ethyl acetate and petroleum ether.
[0018] In the content of the present invention: In the preparation method of the high Tg hydrocarbon resin, the alkyl halide can be any one of p-dichlorobenzyl, 1,4-bis(iodomethyl)benzene, p-phenylenedibromide, p-dibromobenzyl, 4,4-biphenyldichlorobenzyl, 4,4-biphenyldibromobenzyl, 1,6-bis(chloromethyl)naphthalene, 2,7-bis(chloromethyl)naphthalene, 4,4-dibenzylfluorene, 4,4-dibenzylcyclohexane, 2,6-bis(chloromethyl)anthracene and other halogenated aromatic compounds and compounds containing 1 to 4 substituents on the aromatic ring of such halogenated aromatic compounds.
[0019] Another content of the present invention is: a resin composition for high-frequency copper-clad laminates, characterized in that: the resin composition for high-frequency copper-clad laminates comprises 80 to 100 parts by mass of a high-Tg hydrocarbon resin, 0 to 12 parts by mass of a cross-linkable polyphenylene ether resin, 0 to 8 parts by mass of a cyanate resin, 12 to 43 parts by mass of a filler, and 0.09 to 0.8 parts by mass of an initiator;
[0020] In the resin composition for high-frequency copper-clad laminates, the total mass of the high Tg hydrocarbon resin, the cross-linkable polyphenylene ether resin and the cyanate ester resin is 100 parts by mass;
[0021] The high Tg hydrocarbon resin has the general chemical structure formula shown in (I):
[0022]
[0023] In formula (I): n = 0 to 8, R 1 A hydrocarbon group having 6 to 30 carbon atoms and an aromatic ring structure;
[0024] The high Tg hydrocarbon resin is a mixture of compounds having the above chemical structural formula and a polymerization degree n of 0 to 8, wherein the mass proportion (ie, mass percentage) of the compound with n=0 is 35 to 68%.
[0025] The cross-linkable polyphenylene ether resin is a high heat-resistant and low-dielectric polyphenylene ether type bismaleimide resin having a chemical structural formula shown in (II):
[0026]
[0027] In formula (II): n is an integer of 5 to 17, R is a phenyl group or an alkylene group having 2 to 5 carbon atoms;
[0028] The high heat-resistant, low-dielectric polyphenylene ether type bismaleimide resin is a high heat-resistant, low-dielectric polyphenylene ether type bismaleimide resin disclosed in the patent owner "Aiment Chengdu New Materials Technology Co., Ltd.", the Chinese patent number is ZL201910942561.6, the publication number is CN110724261A, and the name is "High heat-resistant, low-dielectric polyphenylene ether type bismaleimide resin, laminate and preparation method thereof".
[0029] The cyanate resin is any one of bisphenol A cyanate resin (ACE for short), bisphenol E cyanate resin (ECE for short), novolac cyanate resin (PCE for short), and dicyclopentadiene bisphenol cyanate resin (DCPDCE for short); the production and supply enterprises of the products include: Yangzhou Wuqiao Resin Factory, Shanghai Huahonghai Chemical Co., Ltd., Zhejiang Jinliyuan Pharmaceutical Co., Ltd., Zhejiang Shangyu Biochemical Co., Ltd., Shanghai Huifeng Science and Trade Co., Ltd., and Swiss Lonza Company;
[0030] The inorganic filler is any one of silicon dioxide, montmorillonite, magnesium oxide, aluminum oxide, mica powder, barium sulfate, kaolin, etc.;
[0031] The initiator is any one of dicumyl peroxide (DCP for short), di-tert-butyl peroxide (DTBP for short), and tert-butyl perbenzoate (CP-01 for short).
[0032] In another aspect of the present invention: the resin composition for high-frequency copper-clad laminates preferably comprises 80 to 100 parts by mass of a high-Tg hydrocarbon resin, 1 to 12 parts by mass of a crosslinkable polyphenylene ether resin, 1 to 8 parts by mass of a cyanate resin, 12 to 43 parts by mass of a filler, and 0.09 to 0.8 parts by mass of an initiator;
[0033] In the resin composition for high-frequency copper-clad laminates, the total mass of the high-Tg hydrocarbon resin, the cross-linkable polyphenylene ether resin and the cyanate ester resin is 100 parts by mass.
[0034] Another aspect of the present invention is a resin composition for high-frequency copper-clad laminates. The preparation method of the resin composition for high-frequency copper-clad laminates is as follows: taking various component raw materials and mixing them uniformly to obtain the resin composition.
[0035] Another content of the present invention is: the use of the resin composition for high-frequency copper-clad laminates, characterized in that: the resin composition for high-frequency copper-clad laminates is mixed with any one of acetone, butanone, cyclohexanone, cyclohexane, methyl isobutyl ketone, toluene, propylene glycol monomethyl ether and the like to prepare a resin solution of the resin composition for copper-clad laminates for preparing prepregs and high-frequency copper-clad laminates.
[0036] The purpose of the resin composition for high-frequency copper-clad laminate is to prepare high-frequency copper-clad laminates. The specific preparation steps of the high-frequency copper-clad laminates are:
[0037] a. Preparation of prepreg: 80-100 parts by weight of high Tg hydrocarbon resin, 0-12 parts by weight of crosslinkable polyphenylene ether resin, 0-8 parts by weight of cyanate resin, 12-43 parts by weight of filler, 0.09-0.3 parts by weight of initiator and (appropriate amount) of solvent are uniformly stirred and mixed to prepare a resin glue solution of epoxy resin composition for copper clad laminate with a solid content of 74%-76%, glass fiber is arranged in the resin glue solution and immersed and then taken out, and most of the solvent is removed by hanging at room temperature, and then placed in an oven at a temperature of 130°C-170°C for baking for 4-7 minutes to obtain a (flame retardant) prepreg;
[0038] In the prepreg, the total mass of the resin component is 100 parts by mass;
[0039] The solvent may be any one of acetone, butanone, cyclohexanone, methyl isobutyl ketone, toluene, propylene glycol monomethyl ether, etc.;
[0040] b. Preparation of high-frequency copper clad laminate: stack 3 to 16 layers of prepregs obtained in step a, attach copper foil on both sides, place in a hot press at 150 to 170°C, gradually pressurize to 0.2 to 4 MPa (depending on the glue flow), press for 0.5 to 1h, then gradually heat to 200 to 220°C and hot press for 4 to 8h, then cool naturally and release the pressure to obtain a high-frequency copper clad laminate.
[0041] The definition of "solid content" described in this article is: the percentage of the mass of non-volatile matter in the total mass of 100g sample (the sample is: epoxy resin composition resin glue for high-frequency copper clad laminate) after baking for 3 hours in an oven at 125°C, and the solid amount finally determined by adding the mass of water solvent is calculated based on the mass of non-volatile matter.
[0042] In the specific preparation steps of the high-frequency copper clad laminate, in step a of preparing a semi-cured sheet, the 0-12 mass parts of cross-linkable polyphenylene ether resin and the 0-8 mass parts of cyanate ester resin are replaced by: 1-12 mass parts of cross-linkable polyphenylene ether resin and 1-8 mass parts of cyanate ester resin.
[0043] Compared with the prior art, the present invention has the following characteristics and beneficial effects:
[0044] (1) The high Tg hydrocarbon resin of the present invention is a compound with a low degree of polymerization (0 to 8). Compared with polyolefin resins with a high degree of polymerization such as polybutadiene and polybutadiene-styrene copolymer, the high Tg hydrocarbon resin of the present invention has good solubility in solvents, good process fluidity, convenient operation, and strong practicality;
[0045] (2) The high Tg hydrocarbon resin of the present invention contains sufficient cross-linking groups and increases the proportion of aromatic structures in the main chain structure, so that the rigidity of the molecular chain of the resin cured product is significantly improved compared with polyolefin resins such as polybutadiene and polybutadiene-styrene copolymer (the main chain is an aliphatic hydrocarbon chain and the aromatic structure is on the side chain), which helps to improve the heat resistance, mechanical strength and dimensional stability of the hydrocarbon resin cured product;
[0046] (3) The resin composition for high-frequency copper-clad laminates in the present application comprises a hydrocarbon resin with a high cross-linking density and a large molecular chain rigidity, so that the obtained copper-clad laminates have excellent dielectric properties, dimensional stability, heat resistance and other properties: dielectric constant of 2.57-2.68 and dielectric loss of 0.0009-0.0013 at 10 GHz; glass transition temperature of 238-251°C, peel strength of 1.09-1.28 N / mm, and bending strength of 63-74 MPa;
[0047] (4) The product of the present invention has a simple preparation process, simple procedures, easy operation and strong practicability. DETAILED DESCRIPTION
[0048] The following embodiments are intended to further illustrate the present invention, but should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by technicians in this field based on the above-mentioned contents of the present invention still fall within the scope of protection of the present invention.
[0049] Part I Preparation of Hydrocarbon Resins (i.e. High Tg Hydrocarbon Resins)
[0050] Example 1-1:
[0051] (1) In a reaction bottle equipped with a stirrer, a thermometer and nitrogen, 1 mol of 5-vinylisophenylene diboronic acid, 1.8 mol of terephthalic dichloride, 1.9 mol of 4-vinylbenzene boronic acid and 2410 g of tetrahydrofuran were added, and stirring was started at room temperature to completely dissolve 5-vinylisophenylene diboronic acid, terephthalic dichloride and 4-vinylbenzene boronic acid, and then 0.02 mol of palladium acetate and 0.0003 mol of phenothiazine were added; 3.6 mol of potassium carbonate was accurately weighed, and a 5 wt% potassium carbonate aqueous solution was prepared with deionized water and added to the reaction bottle, and the reaction was carried out at 50° C. for 8 h. After the reaction was completed, the reaction system was cooled to room temperature, and the organic phase was extracted with an appropriate amount of toluene, washed with a saturated sodium carbonate aqueous solution and washed with water until neutral, and the toluene was evaporated at 75° C. to obtain a hydrocarbon resin. The mass fraction of the compound with n=0 was 25.3% as determined by gel permeation chromatography (GPC).
[0052] Embodiment 1-2:
[0053] (1) In a reaction bottle equipped with a stirrer, a thermometer and nitrogen, 1 mol of 5-vinylisophenyl diboronic acid, 1.8 mol of 4,4-biphenyl dichlorobenzyl, 2.0 mol of 4-vinylbenzene boronic acid and 3294 g of dioxane were added, and stirring was started at room temperature to completely dissolve 5-vinylisophenyl diboronic acid, 4,4-biphenyl dichlorobenzyl and 4-vinylbenzene boronic acid, and then 0.03 mol of palladium acetate and 0.0005 mol of phenothiazine were added; 3.6 mol of potassium carbonate was accurately weighed, and a 5 wt% potassium carbonate aqueous solution was prepared with deionized water and added to the reaction bottle, and the reaction was carried out at 50° C. for 10 h. After the reaction was completed, the reaction system was cooled to room temperature, and the organic phase was extracted with an appropriate amount of toluene, washed with a saturated sodium carbonate aqueous solution and washed with water until neutral, and the toluene was evaporated at 75° C. to obtain a hydrocarbon resin. The mass fraction of the compound with n=0 was 28.8% as determined by gel permeation chromatography (GPC).
[0054] Embodiment 1-3:
[0055] (1) In a reaction bottle equipped with a stirrer, a thermometer and nitrogen, 1 mol of 5-vinylisophenyl diboronic acid, 2.6 mol of 4,4-biphenyl dichlorobenzyl, 3.6 mol of 4-vinylbenzene boronic acid and 5328 g of N-methylpyrrolidone were added, and stirring was started at room temperature to completely dissolve 5-vinylisophenyl diboronic acid, 4,4-biphenyl dichlorobenzyl and 4-vinylbenzene boronic acid, and then 0.05 mol of palladium chloride and 0.0003 mol of phenothiazine were added; 5.2 mol of potassium carbonate was accurately weighed, and a 5 wt% potassium carbonate aqueous solution was prepared with deionized water and added to the reaction bottle, and the reaction was carried out at 60° C. for 10 h. After the reaction was completed, the reaction system was cooled to room temperature, and the organic phase was extracted with an appropriate amount of toluene, washed with a saturated sodium carbonate aqueous solution and washed with water until neutral, and the toluene was evaporated at 75° C. to obtain a hydrocarbon resin. The mass fraction of the compound with n=0 was 67.6% as determined by gel permeation chromatography (GPC).
[0056] Embodiment 1-4:
[0057] (1) In a reaction bottle equipped with a stirrer, a thermometer and nitrogen, 1 mol of 5-vinylisophenyl diboronic acid, 2.2 mol of benzyl chloride, 2.7 mol of 4-vinylbenzene boronic acid and 3905 g of tetrahydrofuran were added, and stirring was started at room temperature to completely dissolve 5-vinylisophenyl diboronic acid, benzyl chloride and 4-vinylbenzene boronic acid, and then 0.04 mol of 4-triphenylphosphine palladium and 0.0004 mol of naphthylamine were added; 4.4 mol of potassium carbonate was accurately weighed, and a 5 wt% potassium carbonate aqueous solution was prepared with deionized water and then added to the reaction bottle, and reacted at 70° C. for 9 h. After the reaction was completed, the reaction system was cooled to room temperature, and the organic phase was extracted with an appropriate amount of toluene, washed with a saturated sodium carbonate aqueous solution and washed with water until neutral, and the toluene was evaporated at 50° C. to obtain a hydrocarbon resin, and the mass fraction of the compound with n=0 was 48.9% by gel permeation chromatography (GPC) detection.
[0058] Part II Preparation of High Frequency Copper Clad Laminate
[0059] Examples 2-1 to 2-6: The steps for preparing a high-frequency copper-clad laminate are:
[0060] (1) 80 to 100 parts by weight of hydrocarbon resin, 0 to 12 parts by weight of crosslinkable polyphenylene ether resin, 0 to 8 parts by weight of cyanate resin, 12 to 43 parts by weight of filler, 0.09 to 0.3 parts by weight of initiator and (appropriate amount) of solvent are uniformly stirred and mixed to prepare an epoxy resin composition resin glue for copper clad laminate with a solid content of 74% to 76%, glass fibers are arranged in the resin glue, immersed and then taken out, suspended at room temperature to remove most of the solvent, and then placed in an oven at a temperature of 130° C. to 170° C. and baked for 4 to 7 minutes to obtain a (flame retardant) prepreg;
[0061] (2) 3 to 16 layers of the semi-cured sheets prepared above are stacked, and copper foil is attached on both sides. They are placed in a hot press at a temperature of 150 to 170°C, and the pressure is gradually increased to 0.2 to 4 MPa (depending on the glue flow), and the pressing is performed for 0.5 to 1 hour. The temperature is then gradually increased to 200 to 220°C and hot pressed for 4 to 8 hours. After natural cooling and pressure relief, a high-frequency copper clad laminate is obtained.
[0062] In the prepreg, the total mass of the resin component is 100 parts by mass; the solvent may be any one of acetone, butanone, cyclohexanone, methyl isobutyl ketone, toluene, propylene glycol monomethyl ether, etc.;
[0063] Table 1: Components, ratios and process parameters of flame-retardant copper-clad laminates of Examples 2-1 to 2-7:
[0064]
[0065] Raw materials used in the examples:
[0066] A1: hydrocarbon resin prepared in Example 1-1;
[0067] A2: hydrocarbon resin prepared in Example 1-2;
[0068] A3: hydrocarbon resin prepared in Example 1-3;
[0069] A4: hydrocarbon resin prepared in Examples 1-4;
[0070] B: Bisphenol A cyanate monomer, Yangzhou Tianqi New Materials Co., Ltd.;
[0071] C: 4-maleimidobenzyl polyphenylene ether, number average molecular weight 1200-1500, the preparation method adopts the preparation method of high heat-resistant low dielectric polyphenylene ether type bismaleimide resin disclosed in the patent owner "Aiment Chengdu New Material Technology Co., Ltd.", patent number ZL201910942561.6, publication number CN110724261A, and title "High heat-resistant low dielectric polyphenylene ether type bismaleimide resin, laminate and preparation method thereof";
[0072] D: dicumyl peroxide, Hongbaoli Group Co., Ltd.;
[0073] E: Silica, Jiangsu Lianrui DQ1040;
[0074] F1: acetone;
[0075] F2: butanone;
[0076] Comparative Example 1:
[0077] 100 parts by mass of polybutadiene resin (Ricon 134), 0.2 parts by mass of dicumyl peroxide and (appropriate amount) of solvent were uniformly stirred and mixed to prepare an epoxy resin composition resin glue for copper clad laminates with a solid content of 74% to 76%. Glass fibers were arranged in the resin glue and immersed and then taken out, and then hung at room temperature to remove most of the solvent, and then placed in an oven at a temperature of 130°C to 170°C for baking for 4 to 7 minutes to obtain a (flame retardant) prepreg; then 12 layers of prepregs were stacked, and copper foils were attached on both sides, and placed in a hot press at a temperature of 150 to 170°C, and gradually pressurized to 0.2 to 4MPa (depending on the glue flow), pressed for 0.5 to 1h, and then gradually heated to 200 to 220°C and hot pressed for 4 to 8h, and then naturally cooled and depressurized to obtain a comparative example 3-1 copper clad laminate.
[0078] Comparative Example 2:
[0079] 100 parts by mass of butadiene-styrene copolymer (Crayville Ricon 181), 0.25 parts by mass of dicumyl peroxide and (appropriate amount) of solvent are uniformly stirred and mixed to prepare an epoxy resin composition resin glue for copper clad laminates with a solid content of 74% to 76%. Glass fibers are arranged in the resin glue and immersed and then taken out, and then hung at room temperature to remove most of the solvent, and then placed in an oven at a temperature of 130°C to 170°C for baking for 4 to 7 minutes to obtain a (flame retardant) prepreg; then 12 layers of prepregs are stacked, and copper foil is attached on both sides, and placed in a hot press at a temperature of 150 to 170°C, and (depending on the glue flow) gradually pressurized to 0.2 to 4MPa, pressed for 0.5 to 1h, and then gradually heated to 200 to 220°C and hot pressed for 4 to 8h, and then naturally cooled and depressurized to obtain a comparative example 3-1 copper clad laminate.
[0080] Table 2 Performance parameters of flame retardant copper clad laminates of Examples 2-1 to 2-7 and Comparative Examples 1 to 2
[0081]
[0082] The relevant standards used in the technical indicators in this article are as follows:
[0083] Glass transition temperature Tg: measured by dynamic mechanical analysis (DMA) according to the DMA method specified in 2.4.24.4 of IPC-TM-650;
[0084] Dielectric constant Dk and dielectric loss Df: Use SPDR method to test 10GHz data according to the method specified in IEC 61189-2-721;
[0085] CTE (Z-axis expansion coefficient): Tested according to the method specified in 2.4.24.5 of IPC-TM-6501;
[0086] Peel strength: Test the peel strength of the metal cover layer according to the experimental conditions of "thermal stress" in the method specified in 2.4.8 of IPC-TM-650;
[0087] Bending strength: Test the bending strength of the copper clad laminate according to the method specified in 2.4.4 of IPC-TM-650.
[0088] Thermal delamination time T300: measured according to the method specified in 2.4.24.1 of IPC-TM-650;
[0089] Embodiment 3:
[0090] A high Tg hydrocarbon resin, wherein the high Tg hydrocarbon resin has the general chemical structure shown in (I):
[0091]
[0092] In formula (I): n = 0 to 8, R 1 A hydrocarbon group having 6 to 30 carbon atoms and containing an aromatic ring structure;
[0093] The high Tg hydrocarbon resin is a mixture of compounds having the above chemical structural formula and a polymerization degree n of 0 to 8, wherein the mass proportion (ie, mass percentage) of the compound with n=0 is 25 to 68%.
[0094] Embodiment 4:
[0095] A method for preparing a high Tg hydrocarbon resin comprises the following steps:
[0096] In a reaction bottle equipped with a stirrer, a thermometer and nitrogen, add 1 mol of vinylbenzene diboric acid, 1.8 mol of alkyl halide, 1.05 times the molar amount of end-capping agent of alkyl halide, and 2 times the total mass of solvent A of alkyl halide and vinylbenzene diboric acid, start stirring at room temperature to dissolve alkyl halide, vinylbenzene diboric acid and end-capping agent (completely), then add 2% of the molar amount of vinylbenzene diboric acid catalyst and 0.03% of the molar amount of vinylbenzene diboric acid inhibitor; (accurately) weigh 2 times the molar amount of alkyl halide, prepare the accelerator into an accelerator aqueous solution with a mass percentage concentration of 5% with deionized water and add it to the reaction bottle, and react at 50°C for 20 hours. After the reaction is completed, wait for the reaction system to cool to room temperature, extract the organic phase with solvent B, wash with saturated sodium carbonate aqueous solution, wash with water until neutral, and evaporate solvent B at 50-75°C to obtain a high Tg hydrocarbon resin.
[0097] Embodiment 5:
[0098] A method for preparing a high Tg hydrocarbon resin comprises the following steps:
[0099] In a reaction bottle equipped with a stirrer, a thermometer and nitrogen, add 1 mol of vinylbenzene diboric acid, 2.6 mol of alkyl halide, 1.45 times the molar amount of end-capping agent of alkyl halide, and 10 times the total mass of solvent A of alkyl halide and vinylbenzene diboric acid, start stirring at room temperature to dissolve alkyl halide, vinylbenzene diboric acid and end-capping agent (completely), then add 6% of the molar amount of vinylbenzene diboric acid catalyst and 0.2% of the molar amount of vinylbenzene diboric acid inhibitor; (accurately) weigh 2 times the molar amount of alkyl halide, prepare the accelerator into an accelerator aqueous solution with a mass percentage concentration of 5% with deionized water and add it to the reaction bottle, and react at 80°C for 8h. After the reaction is completed, wait for the reaction system to cool to room temperature, extract the organic phase with solvent B, wash with saturated sodium carbonate aqueous solution, wash with water until neutral, and evaporate solvent B at 50-75°C to obtain high Tg hydrocarbon resin.
[0100] Embodiment 6:
[0101] A method for preparing a high Tg hydrocarbon resin comprises the following steps:
[0102] In a reaction bottle equipped with a stirrer, a thermometer and nitrogen, add 1 mol of vinylbenzene diboric acid, 2.2 mol of alkyl halide, 1.25 times the molar amount of end-capping agent of alkyl halide, and 6 times the total mass of solvent A of alkyl halide and vinylbenzene diboric acid, start stirring at room temperature to dissolve alkyl halide, vinylbenzene diboric acid and end-capping agent (completely), then add 4% of the molar amount of vinylbenzene diboric acid catalyst and 0.11% of the molar amount of vinylbenzene diboric acid inhibitor; (accurately) weigh 2 times the molar amount of alkyl halide, prepare the accelerator into an accelerator aqueous solution with a mass percentage concentration of 5% with deionized water and add it to the reaction bottle, and react at 65°C for 14 hours. After the reaction is completed, wait for the reaction system to cool to room temperature, extract the organic phase with solvent B, wash with saturated sodium carbonate aqueous solution, wash with water until neutral, and evaporate solvent B at 50-75°C to obtain high Tg hydrocarbon resin.
[0103] In the above-mentioned embodiments 4-6:
[0104] The vinylphenyl diboronic acid is 5-vinylisophenyl diboronic acid;
[0105] The alkyl halide is a compound having 6 to 30 carbon atoms, containing an aromatic ring structure and being disubstituted by halogen; specifically, it can be: p-dichlorobenzyl, 1,4-bis(iodomethyl)benzene, p-phenylenedibromide, p-dibromobenzyl, 4,4-biphenyldichlorobenzyl, 4,4-biphenyldibromobenzyl, 1,6-bis(chloromethyl)naphthalene, 2,7-bis(chloromethyl)naphthalene, 4,4-dibenzylfluorene, 4,4-dibenzylcyclohexane, 2,6-bis(chloromethyl)anthracene and other halogenated aromatic compounds, and any of the compounds having 1 to 4 substituents on the aromatic ring of such halogenated aromatic compounds;
[0106] The solvent A is any one of methanol, ethanol, tetrahydrofuran, dioxane, dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone;
[0107] The catalyst is any one of palladium chloride, palladium acetate, 4-triphenylphosphine palladium, carbene palladium, and ferrocene palladium dichloride;
[0108] The polymerization inhibitor is a hindered amine, which is any one of phenothiazine, 2,2,6,6-tetramethylpiperidine, p-phenylenediamine, naphthylamine, diphenylamine, 4-methylpyrimidine, N,N-diethyl-p-phenylenediamine, N,N-diphenyl-p-phenylenediamine, dioctyl diphenylamine, N-methyl-α-naphthylamine, etc.;
[0109] The end-capping agent is 3-vinylbenzene boronic acid or 4-vinylbenzene boronic acid;
[0110] The solvent B is any one of toluene, xylene, methyl isobutyl ketone, ethyl acetate and petroleum ether.
[0111] Embodiment 7:
[0112] The invention discloses a resin composition for high-frequency copper-clad laminates, which is composed of 100 parts by mass of a high-Tg hydrocarbon resin, 12 parts by mass of a filler and 0.09 parts by mass of an initiator which are uniformly mixed.
[0113] Embodiment 8:
[0114] The invention discloses a resin composition for high-frequency copper-clad laminates, which is composed of 100 parts by mass of a high-Tg hydrocarbon resin, 43 parts by mass of a filler and 0.8 parts by mass of an initiator which are uniformly mixed.
[0115] Embodiment 9:
[0116] The invention discloses a resin composition for high-frequency copper-clad laminates, which is composed of 100 parts by mass of a high-Tg hydrocarbon resin, 28 parts by mass of a filler and 0.45 parts by mass of an initiator which are uniformly mixed.
[0117] Embodiment 10:
[0118] The resin composition for high-frequency copper-clad laminates is composed of 98 parts by mass of a high-Tg hydrocarbon resin, 1 part by mass of a cross-linkable polyphenylene ether resin, 1 part by mass of a cyanate resin, 12 parts by mass of a filler, and 0.09 parts by mass of an initiator, which are uniformly mixed.
[0119] Embodiment 11:
[0120] The resin composition for high-frequency copper-clad laminates is composed of 80 parts by mass of high-Tg hydrocarbon resin, 12 parts by mass of cross-linkable polyphenylene ether resin, 8 parts by mass of cyanate resin, 43 parts by mass of filler, and 0.8 parts by mass of initiator, which are uniformly mixed.
[0121] Embodiment 12:
[0122] The resin composition for high-frequency copper-clad laminates is composed of 90 parts by mass of a high-Tg hydrocarbon resin, 6 parts by mass of a cross-linkable polyphenylene ether resin, 4 parts by mass of a cyanate resin, 27 parts by mass of a filler, and 0.4 parts by mass of an initiator, which are uniformly mixed.
[0123] In the above-mentioned embodiments 7-12:
[0124] The high Tg hydrocarbon resin has the general chemical structure formula shown in (I):
[0125]
[0126] In formula (I): n = 0 to 8, R 1 A hydrocarbon group having 6 to 30 carbon atoms and an aromatic ring structure;
[0127] The high Tg hydrocarbon resin is a mixture of compounds having the above-mentioned general chemical structure and a polymerization degree n of 0 to 8, wherein the mass proportion (i.e., mass percentage) of the compound with n=0 is 35 to 68%;
[0128] The cross-linkable polyphenylene ether resin is a high heat-resistant and low-dielectric polyphenylene ether type bismaleimide resin having a chemical structural formula shown in (II):
[0129]
[0130]
[0131] In formula (II): n is an integer of 5 to 17, R is a phenyl group or an alkylene group having 2 to 5 carbon atoms;
[0132] The high heat-resistant and low dielectric polyphenylene ether bismaleimide resin is a high heat-resistant and low dielectric polyphenylene ether bismaleimide resin disclosed in the patent owner "Aimengte Chengdu New Materials Technology Co., Ltd.", the Chinese patent number is ZL201910942561.6, the publication number is CN110724261A, and the name is "High Heat-resistant and Low Dielectric Polyphenylene Ether Bismaleimide Resin, Laminated Board and Preparation Method thereof";
[0133] The cyanate resin is any one of bisphenol A cyanate resin (ACE for short), bisphenol E cyanate resin (ECE for short), novolac cyanate resin (PCE for short), and dicyclopentadiene bisphenol cyanate resin (DCPDCE for short); the production and supply enterprises of the products include: Yangzhou Wuqiao Resin Factory, Shanghai Huahonghai Chemical Co., Ltd., Zhejiang Jinliyuan Pharmaceutical Co., Ltd., Zhejiang Shangyu Biochemical Co., Ltd., Shanghai Huifeng Science and Trade Co., Ltd., and Swiss Lonza Company;
[0134] The inorganic filler is any one of silicon dioxide, montmorillonite, magnesium oxide, aluminum oxide, mica powder, barium sulfate, kaolin, etc.;
[0135] The initiator is any one of dicumyl peroxide (DCP for short), di-tert-butyl peroxide (DTBP for short), and tert-butyl perbenzoate (CP-01 for short).
[0136] Embodiment 13:
[0137] The use of the above-mentioned resin composition for high-frequency copper-clad laminates is characterized in that the resin composition for high-frequency copper-clad laminates is mixed with any one of solvents such as acetone, butanone, cyclohexanone, cyclohexane, methyl isobutyl ketone, toluene, propylene glycol monomethyl ether, etc. to prepare a resin solution of the resin composition for copper-clad laminates, which is used to prepare prepregs and high-frequency copper-clad laminates.
[0138] Embodiment 14:
[0139] The use of the resin composition for high-frequency copper-clad laminates is to prepare high-frequency copper-clad laminates. The specific preparation steps of the high-frequency copper-clad laminates are as follows:
[0140] a. Preparation of prepreg: 100 parts by mass of high Tg hydrocarbon resin, 12 parts by mass of filler, 0.09 parts by mass of initiator and (appropriate amount) of solvent are uniformly stirred and mixed to prepare epoxy resin composition resin glue for copper clad laminate with a solid content of 74%, glass fiber is arranged in the resin glue and immersed, then taken out, hung at room temperature to remove most of the solvent, and then placed in an oven at a temperature of 130° C. and baked for 7 minutes to obtain a (flame retardant) prepreg;
[0141] The solvent may be any one of acetone, butanone, cyclohexanone, methyl isobutyl ketone, toluene, propylene glycol monomethyl ether, etc.;
[0142] b. Preparation of high-frequency copper-clad laminate: stack three layers of prepregs obtained in step a, attach copper foil on both sides, place in a hot press at 150°C, gradually pressurize to 0.2MPa (depending on the glue flow), press for 1h, then gradually heat to 200°C and hot press for 8h, then naturally cool and release the pressure to obtain a high-frequency copper-clad laminate.
[0143] Embodiment 15:
[0144] The use of the resin composition for high-frequency copper-clad laminates is to prepare high-frequency copper-clad laminates. The specific preparation steps of the high-frequency copper-clad laminates are as follows:
[0145] a. Preparation of prepreg: 100 parts by mass of high Tg hydrocarbon resin, 43 parts by mass of filler, 0.3 parts by mass of initiator and (appropriate amount) of solvent are uniformly stirred and mixed to prepare epoxy resin composition resin glue for copper clad laminate with a solid content of 76%, glass fiber is arranged in the resin glue and immersed, then taken out, hung at room temperature to remove most of the solvent, and then placed in an oven at a temperature of 170°C for 4 minutes to obtain a (flame retardant) prepreg;
[0146] The solvent may be any one of acetone, butanone, cyclohexanone, methyl isobutyl ketone, toluene, propylene glycol monomethyl ether, etc.;
[0147] b. Preparation of high-frequency copper clad laminate: stack 16 layers of prepregs obtained in step a, attach copper foil on both sides, place in a hot press at 170°C, gradually pressurize to 4MPa (depending on the glue flow), press for 0.5h, then gradually heat to 220°C and hot press for 4h, then naturally cool and release the pressure to obtain a high-frequency copper clad laminate.
[0148] Embodiment 16:
[0149] The use of the resin composition for high-frequency copper-clad laminates is to prepare high-frequency copper-clad laminates. The specific preparation steps of the high-frequency copper-clad laminates are as follows:
[0150] a. Preparation of prepreg: 100 parts by mass of high Tg hydrocarbon resin, 27.5 parts by mass of filler, 0.18 parts by mass of initiator and (appropriate amount) of solvent are uniformly stirred and mixed to prepare a resin glue solution of epoxy resin composition for copper clad laminate with a solid content of 75%, glass fiber is arranged in the resin glue solution and immersed, then taken out, hung at room temperature to remove most of the solvent, and then placed in an oven at a temperature of 150° C. and baked for 6 minutes to obtain a (flame retardant) prepreg;
[0151] The solvent may be any one of acetone, butanone, cyclohexanone, methyl isobutyl ketone, toluene, propylene glycol monomethyl ether, etc.;
[0152] b. Preparation of high-frequency copper clad laminate: stack 10 layers of prepregs obtained in step a, attach copper foil on both sides, place in a hot press at 160°C, gradually pressurize to 0.3MPa (depending on the glue flow), press for 0.8h, then gradually heat to 210°C and hot press for 6h, then naturally cool and release the pressure to obtain a high-frequency copper clad laminate.
[0153] Embodiment 17:
[0154] The use of the resin composition for high-frequency copper-clad laminates is to prepare high-frequency copper-clad laminates. The specific preparation steps of the high-frequency copper-clad laminates are as follows:
[0155] a. Preparation of prepreg: 98 parts by mass of high Tg hydrocarbon resin, 1 part by mass of crosslinkable polyphenylene ether resin, 1 part by mass of cyanate resin, 43 parts by mass of filler, 0.3 part by mass of initiator and (appropriate amount) of solvent are uniformly stirred and mixed to prepare epoxy resin composition resin glue for copper clad laminate with a solid content of 76%, glass fiber is arranged in the resin glue, immersed and taken out, hung at room temperature to remove most of the solvent, and then placed in an oven at a temperature of 170°C for 4 minutes to obtain a (flame retardant) prepreg;
[0156] The solvent may be any one of acetone, butanone, cyclohexanone, methyl isobutyl ketone, toluene, propylene glycol monomethyl ether, etc.;
[0157] b. Preparation of high-frequency copper clad laminate: stack 16 layers of prepregs obtained in step a, attach copper foil on both sides, place in a hot press at 170°C, gradually pressurize to 4MPa (depending on the glue flow), press for 0.5h, then gradually heat to 220°C and hot press for 4h, then naturally cool and release the pressure to obtain a high-frequency copper clad laminate.
[0158] Embodiment 18:
[0159] The use of the resin composition for high-frequency copper-clad laminates is to prepare high-frequency copper-clad laminates. The specific preparation steps of the high-frequency copper-clad laminates are as follows:
[0160] a. Preparation of prepreg: 80 parts by mass of high Tg hydrocarbon resin, 12 parts by mass of crosslinkable polyphenylene ether resin, 8 parts by mass of cyanate resin, 12 parts by mass of filler, 0.09 parts by mass of initiator and (appropriate amount) of solvent are uniformly stirred and mixed to prepare epoxy resin composition resin glue for copper clad laminate with a solid content of 74%, glass fiber is arranged in the resin glue and immersed, then taken out, hung at room temperature to remove most of the solvent, and then placed in an oven at a temperature of 130°C for 7 minutes to obtain a (flame retardant) prepreg;
[0161] The solvent may be any one of acetone, butanone, cyclohexanone, methyl isobutyl ketone, toluene, propylene glycol monomethyl ether, etc.;
[0162] b. Preparation of high-frequency copper-clad laminate: stack three layers of prepregs obtained in step a, attach copper foil on both sides, place in a hot press at 150°C, gradually pressurize to 0.2MPa (depending on the glue flow), press for 1h, then gradually heat to 200°C and hot press for 8h, then naturally cool and release the pressure to obtain a high-frequency copper-clad laminate.
[0163] Embodiment 19:
[0164] The use of the resin composition for high-frequency copper-clad laminates is to prepare high-frequency copper-clad laminates. The specific preparation steps of the high-frequency copper-clad laminates are as follows:
[0165] a. Preparation of prepreg: 90 parts by mass of high Tg hydrocarbon resin, 6 parts by mass of crosslinkable polyphenylene ether resin, 4 parts by mass of cyanate resin, 27.5 parts by mass of filler, 0.19 parts by mass of initiator and (appropriate amount) of solvent are uniformly stirred and mixed to prepare epoxy resin composition resin glue for copper clad laminate with a solid content of 75%, glass fiber is arranged in the resin glue and immersed, then taken out, hung at room temperature to remove most of the solvent, and then placed in an oven at a temperature of 150°C for baking for 5.5 minutes to obtain a (flame retardant) prepreg;
[0166] The solvent may be any one of acetone, butanone, cyclohexanone, methyl isobutyl ketone, toluene, propylene glycol monomethyl ether, etc.;
[0167] b. Preparation of high-frequency copper clad laminate: stack 9 layers of prepregs obtained in step a, attach copper foil on both sides, place in a hot press at 160°C, gradually pressurize to 2.1MPa (depending on the glue flow), press for 0.75h, then gradually heat to 210°C and hot press for 6h, then naturally cool and release the pressure to obtain a high-frequency copper clad laminate.
[0168] In the above embodiment, the definition of "solid content" is: the percentage of the mass of non-volatile matter in the total mass of 100g sample (i.e., epoxy resin composition resin glue for high-frequency copper clad laminate) after baking for 3 hours in an oven at 125°C, and the solid amount finally determined by adding the mass of water solvent is calculated based on the mass of the non-volatile matter.
[0169] In the above embodiments: the percentages used, unless otherwise specified, are all mass (weight) percentages or percentages known to those skilled in the art; the proportions used, unless otherwise specified, are all mass (weight) proportions; and the weights may be in grams or kilograms.
[0170] In the above embodiments, the process parameters (temperature, time, concentration, etc.) in each step and the numerical values of the amounts of each component are ranges, and any point can be applied.
[0171] The technical contents not specifically described in the present invention and the above embodiments are the same as the prior art, and the raw materials are all commercially available products.
[0172] The present invention is not limited to the above embodiments, and all of the contents of the present invention can be implemented and have the above good effects.
Claims
1. A high Tg hydrocarbon resin, characterized in that: The high Tg hydrocarbon resin has the general chemical structure formula shown in (I): In formula (I), n=0-8, R1 is a hydrocarbon group having 6-30 carbon atoms and containing an aromatic ring structure; The high Tg hydrocarbon resin is a mixture of compounds having the above-mentioned general chemical structure and a polymerization degree n of 0 to 8, wherein the mass proportion of the compound with n=0 is 25 to 68%; The preparation method of the high Tg hydrocarbon resin comprises: adding 1 mol of vinylbenzene diboric acid, 1.8 to 2.6 mol of alkyl halide, 1.05 to 1.45 times the molar amount of end-capping agent of alkyl halide, and 2 to 10 times the total mass of solvent A of alkyl halide and vinylbenzene diboric acid into a reaction bottle equipped with a stirrer, a thermometer and nitrogen; stirring is started at room temperature to dissolve the alkyl halide, vinylbenzene diboric acid and end-capping agent; and then adding a catalyst with a molar amount of 2% to 6% of vinylbenzene diboric acid, vinylbenzene diboric acid and the like. a polymerization inhibitor of 0.03% to 0.2% of diboric acid molar amount; a promoter of 2 times the molar amount of alkyl halide is weighed, the promoter is prepared into a promoter aqueous solution with a mass percentage concentration of 5% with deionized water and added to a reaction bottle, and the reaction is carried out at a temperature of 50 to 80° C. for 8 to 20 hours; after the reaction is completed, the reaction system is cooled to room temperature, the organic phase is extracted with solvent B, washed with saturated sodium carbonate aqueous solution, washed with water until neutral, and solvent B is evaporated at a temperature of 50 to 75° C. to obtain a high Tg hydrocarbon resin; The vinylphenyl diboronic acid is 5-vinylisophenyl diboronic acid; The alkyl halide is any one of terephthalene dichlorobenzyl and 4,4-biphenyl dichlorobenzyl; The solvent A is any one of methanol, ethanol, tetrahydrofuran, dioxane, dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone; The catalyst is any one of palladium chloride, palladium acetate, 4-triphenylphosphine palladium, carbene palladium, and ferrocene palladium dichloride; The polymerization inhibitor is a hindered amine, which is any one of phenothiazine, 2,2,6,6-tetramethylpiperidine, p-phenylenediamine, naphthylamine, diphenylamine, 4-methylpyrimidine, N,N-diethyl-p-phenylenediamine, N,N-diphenyl-p-phenylenediamine, dioctyl diphenylamine, and N-methyl-α-naphthylamine; The end-capping agent is 3-vinylbenzene boronic acid or 4-vinylbenzene boronic acid; The solvent B is any one of toluene, xylene, methyl isobutyl ketone, ethyl acetate and petroleum ether.
2. A resin composition for high-frequency copper-clad laminate, characterized in that: The resin composition for high-frequency copper-clad laminates comprises 80 to 100 parts by mass of a high-Tg hydrocarbon resin, 0 to 12 parts by mass of a cross-linkable polyphenylene ether resin, 0 to 8 parts by mass of a cyanate resin, 12 to 43 parts by mass of a filler, and 0.09 to 0.8 parts by mass of an initiator; In the resin composition for high-frequency copper-clad laminates, the total mass of the high Tg hydrocarbon resin, the cross-linkable polyphenylene ether resin and the cyanate ester resin is 100 parts by mass; The high Tg hydrocarbon resin has the general chemical structure formula shown in (I): In formula (I), n=0-8, R1 is a hydrocarbon group having 6-30 carbon atoms and containing an aromatic ring structure; The high Tg hydrocarbon resin is a mixture of compounds having the above-mentioned general chemical structure and a polymerization degree n of 0 to 8, wherein the mass proportion of the compound with n=0 is 35 to 68%; The preparation method of the high Tg hydrocarbon resin comprises: adding 1 mol of vinylbenzene diboric acid, 1.8 to 2.6 mol of alkyl halide, 1.05 to 1.45 times the molar amount of end-capping agent of alkyl halide, and 2 to 10 times the total mass of solvent A of alkyl halide and vinylbenzene diboric acid into a reaction bottle equipped with a stirrer, a thermometer and nitrogen; stirring is started at room temperature to dissolve the alkyl halide, vinylbenzene diboric acid and end-capping agent; and then adding a catalyst with a molar amount of 2% to 6% of vinylbenzene diboric acid, vinylbenzene diboric acid and the like. a polymerization inhibitor of 0.03% to 0.2% of diboric acid molar amount; a promoter of 2 times the molar amount of alkyl halide is weighed, the promoter is prepared into a promoter aqueous solution with a mass percentage concentration of 5% with deionized water and added to a reaction bottle, and the reaction is carried out at a temperature of 50 to 80° C. for 8 to 20 hours; after the reaction is completed, the reaction system is cooled to room temperature, the organic phase is extracted with solvent B, washed with saturated sodium carbonate aqueous solution, washed with water until neutral, and solvent B is evaporated at a temperature of 50 to 75° C. to obtain a high Tg hydrocarbon resin; The vinylphenyl diboronic acid is 5-vinylisophenyl diboronic acid; The alkyl halide is any one of terephthalene dichlorobenzyl and 4,4-biphenyl dichlorobenzyl; The solvent A is any one of methanol, ethanol, tetrahydrofuran, dioxane, dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone; The catalyst is any one of palladium chloride, palladium acetate, 4-triphenylphosphine palladium, carbene palladium, and ferrocene palladium dichloride; The polymerization inhibitor is a hindered amine, which is any one of phenothiazine, 2,2,6,6-tetramethylpiperidine, p-phenylenediamine, naphthylamine, diphenylamine, 4-methylpyrimidine, N,N-diethyl-p-phenylenediamine, N,N-diphenyl-p-phenylenediamine, dioctyl diphenylamine, and N-methyl-α-naphthylamine; The end-capping agent is 3-vinylbenzene boronic acid or 4-vinylbenzene boronic acid; The solvent B is any one of toluene, xylene, methyl isobutyl ketone, ethyl acetate, and petroleum ether; The cross-linkable polyphenylene ether resin is a high heat-resistant and low-dielectric polyphenylene ether type bismaleimide resin having a chemical structural formula shown in (II): In formula (II): n is an integer of 5 to 17, R is a phenyl group or an alkylene group having 2 to 5 carbon atoms; The cyanate resin is any one of bisphenol A cyanate resin, bisphenol E cyanate resin, phenolic cyanate resin, and dicyclopentadiene bisphenol cyanate resin; The filler is any one of silicon dioxide, montmorillonite, magnesium oxide, aluminum oxide, mica powder, barium sulfate, and kaolin; The initiator is any one of dicumyl peroxide, di-tert-butyl peroxide and tert-butyl perbenzoate.
3. The resin composition for high-frequency copper-clad laminate according to claim 2, characterized in that: The resin composition for high-frequency copper-clad laminates comprises 80 to 100 parts by mass of a high-Tg hydrocarbon resin, 1 to 12 parts by mass of a cross-linkable polyphenylene ether resin, 1 to 8 parts by mass of a cyanate resin, 12 to 43 parts by mass of a filler, and 0.09 to 0.8 parts by mass of an initiator; In the resin composition for high-frequency copper-clad laminates, the total mass of the high-Tg hydrocarbon resin, the cross-linkable polyphenylene ether resin and the cyanate ester resin is 100 parts by mass.
4. The use of the resin composition for high-frequency copper-clad laminate according to claim 2, characterized in that: The resin composition for high-frequency copper-clad laminate is prepared by mixing any one of acetone, butanone, cyclohexanone, cyclohexane, methyl isobutyl ketone, toluene and propylene glycol monomethyl ether to prepare a resin solution for the resin composition for copper-clad laminate, which is used for preparing prepregs and high-frequency copper-clad laminates.
5. The use of the resin composition for high-frequency copper-clad laminate according to claim 4, characterized in that: The specific preparation steps of the high-frequency copper clad laminate are: a. Preparation of prepreg: 80-100 parts by weight of high Tg hydrocarbon resin, 0-12 parts by weight of crosslinkable polyphenylene ether resin, 0-8 parts by weight of cyanate resin, 12-43 parts by weight of filler, 0.09-0.3 parts by weight of initiator and solvent are uniformly stirred and mixed to prepare a resin glue solution of epoxy resin composition for copper clad laminate with a solid content of 74%-76%, glass fiber is arranged in the resin glue solution and immersed, then taken out, hung at room temperature to remove most of the solvent, and then placed in an oven at a temperature of 130°C-170°C for 4-7 minutes to prepare a prepreg; In the prepreg, the total mass of the resin component is 100 parts by mass; The solvent is any one of acetone, butanone, cyclohexanone, cyclohexane, methyl isobutyl ketone, toluene, and propylene glycol monomethyl ether; b. Preparation of high-frequency copper clad laminate: stack 3 to 16 layers of prepregs obtained in step a, attach copper foil on both sides, place in a hot press at 150 to 170°C, gradually pressurize to 0.2 to 4 MPa, press for 0.5 to 1h, then gradually heat to 200 to 220°C and hot press for 4 to 8h, then naturally cool and release the pressure to obtain a high-frequency copper clad laminate.
6. The use of the resin composition for high-frequency copper-clad laminate according to claim 5, characterized in that: In the step a of preparing the prepreg, the 0-12 mass parts of the crosslinkable polyphenylene ether resin and the 0-8 mass parts of the cyanate ester resin are replaced by 1-12 mass parts of the crosslinkable polyphenylene ether resin and 1-8 mass parts of the cyanate ester resin.
Citation Information
Patent Citations
Prepreg and its application products for low thermal expansion and low dielectric tangent
CN101692756A
High-heat-resistant low-dielectric polyphenylether dimaleimide resin, laminated board and preparation method of high-heat-resistant low-dielectric polyphenylether dimaleimide resin
CN110724261A
Method for preparing high-speed copper-clad plate from bismaleimide modified hydrocarbon resin
CN114589991A
Compound, mixture, curable resin composition and cured product thereof, and method for manufacturing compound
CN114650979A